Intervention to reduce unnecessary urinary catheter use in a large academic health science centre: A one‐group, pretest, posttest study with a theory‐based process evaluation - Chantal Backman; Krista R. Wooller; Delvina Hasimja‐Saraqini; Melissa Demery Varin; Michelle Crick; Danielle Cho‐Young; Lisa Freeman; Lori Delaney; Janet E. Squires (Wiley, 2022)
Abstract Aim To evaluate an intervention to reduce unnecessary urinary catheter use and prevent catheter‐associated urinary‐tract infections (CAUTI) in hospitalized patients across an academic health science centre. Methods We conducted a one‐group, pretest, posttest study with a theory‐based process evaluation. Phase 1 consisted of a pre/postintervention to test the impact of a CAUTI protocol. Audits on four units were conducted, and data were analysed descriptively. Phase 2 consisted of a theory‐based process evaluation to understand the barriers/enablers to the implementation. Semistructured interviews were conducted and then analysed using a systematic approach. Results In Phase 1, all inpatients with urinary catheters admitted to the units (N = 4) during the study period (N = 99, pre) and (N = 99, post) were included. CAUTI prevalence rate was 18.2% pre versus 14.1% post (p = .563). In Phase 2, participants (N = 18) who worked on the units were interviewed, and a total of 13 barriers and 19 enablers were found.